The signalling and function of EB12 in the central nervous system - Rutkowska, Aleksandra (Trinity College (Dublin, Ireland). Department of Physiology, 2014)
The four major brain-specific cell types in the brain are; (i) neurons, which transmit and process information via electrical signals, (ii) oligodendrocytes, which insulate neuronal axons with fatty sheets called myelin to ensure fast and complete electrical signal transduction, (iii) microglia, which provide defence against potential infections in the brain and, (iv) astrocytes, that serve many important roles such as immune defence, cleaning up debris, ensuring proper neuronal functioning and also communication with other cells. These cells, and indeed all living cells, have a wide range of proteins called receptors on their surface, which are activated by signalling molecules. EBI2 is one such receptor that plays very important roles in the biology of immune cells, where it regulates antibody production to fight infections.
Keywords: Molecular Neuropharmacology, Ph.D.; Ph.D. Trinity College Dublin